Lipogems Product Treatment Increases the Proliferation Rate of Human Tendon Stem Cells without Affecting Their Stemness and Differentiation Capability - Pietro Randelli; Alessandra Menon; Vincenza Ragone; Pasquale Creo; Sonia Bergante; Filippo Randelli; Laura De Girolamo; Umberto Alfieri Montrasio; Giuseppe Banfi; Paolo Cabitza; Guido Tettamanti; Luigi Anastasia (Stem Cells International)
Increasing the success rate of rotator cuff healing remains tremendous challenge. Among many approaches, the possibility of activating resident stem cells in situ, without the need to isolate them from biopsies, could represent valuable therapeutic strategy. Along this line, it has been recently demonstrated that lipoaspirate product, Lipogems, contains and produces growth-factors that may activate resident stem cells. In this study, human tendon stem cells (hTSCs) from the rotator cuff were cocultured in a transwell system with the Lipogems lipoaspirate product and compared to control untreated cells in terms of cell proliferation, morphology, stem cell marker and VEGF expression, and differentiation and migration capabilities. Results showed that the Lipogems product significantly increases the proliferation rate of hTSCs without altering their stemness and differentiation capability. Moreover, treated cells increase the expression of VEGF, which is crucial for the neovascularization of the tissue during the healing process. Overall, this study supports that directly activating hTSCs with the Lipogems lipoaspirate could represent a new practical therapeutic approach. In fact, obtaining a lipoaspirate is easier, safer, and more cost-effective than harvesting cells from tendon or bone marrow biopsies, expanding them in GMP facility and then reinjecting them in the patient.